Ferroptosis in Acute Central Nervous System Injuries: The Future Direction? - Shen, Lesang; Lin, Danfeng; Li, Xiaoyi; Wu, Haijian; Lenahan, Cameron; Pan, Yuanbo; Xu, Weilin; Chen, Yiding; Shao, Anwen; Zhang, Jianmin (Frontiers in Cell and Developmental Biology, 2020)
Acute central nervous system (CNS) injuries, such as stroke, traumatic brain injury, and spinal cord injury present a grave health care challenge worldwide due to high morbidity and mortality, as well as limited clinical therapeutic strategies. Established literature has shown that oxidative stress, inflammation, excitotoxicity, and apoptosis play important roles in the pathophysiological processes of acute CNS injuries. Recently, there have been many studies on the topic of ferroptosis, a form of regulated cell death characterized by the accumulation of iron-dependent lipid peroxidation. Some studies have revealed an emerging connection between acute CNS injuries and ferroptosis. Ferroptosis, induced by the abnormal metabolism of lipids, glutathione, and iron, can accelerate acute CNS injuries. However, pharmaceutical agents, such as iron chelators, ferrostatin-1, and liproxstatin-1, can inhibit ferroptosis and may have neuroprotective effects after acute CNS injuries. However, the specific mechanisms underlying this connection has not yet been clearly elucidated. In this paper, we discuss the general mechanisms of ferroptosis and its role in stroke, traumatic brain injury, and spinal cord injury. We also summarize ferroptosis-related drugs and highlight the potential therapeutic strategies in treating various acute CNS injuries. Additionally, this paper suggests a testable hypothesis that ferroptosis may be a novel direction for further research of acute CNS injuries by providing corresponding evidence.